Adenylate cyclase inhibition is required for normal redistribution of platelet surface GPIb in response to PAR1 activation. Issue 173 (January 2019) - Pouget, Thomas; Pillois, Xavier; Fiore, Mathieu
Highlights: Thrombin activates human platelets by hydrolyzing PAR receptors. Surface GPIb transiently decreases when platelets are stimulated by PAR agonists. We investigated whether ADP signaling potentiates PAR-induced GPIb redistribution. GPIb clearance induced by PAR1 involves inhibition of adenylyl cyclase via P2Y12 .